P114Role of atrial remodeling in reentrant dynamics during in-vitro atrial fibrillation. (15th July 2014) - Climent, A.M; Guillem, M.S; Lee, P; Bollensdorff, C; Fernandez-Santos, M.E; Sanz-Ruiz, R; Sanchez, PL; Atienza, F; Fernandez-Aviles, F
Abstract: Introduction: The role of tissue remodeling in the reentrant activity during atrial fibrillation (AF) is not well understood. The aim of this study is to evaluate in an in-vitro model of AF the role of tissue remodeling in the mechanisms of perpetuation of this arrhythmia. Methods: HL-1 cultures were obtained for early stage (6.1 ± 1.3 days in culture, N=10) and late stage (11.7 ± 0.5 days in culture, N=8) AF. Bright field images together with optical calcium mapping (Rhod-2AM staining) were obtained for evaluating remodeling and electrophysiological characteristics of cell cultures. Results: The number of singularity points per square centimeter at baseline was significantly higher in the late stage group (i.e. 0.43±0.19 vs. 1.12±0.14 PS/cm2, p <0.01) and showed an inverse correlation with the degree of homogeneity in the corresponding bright field microscopy images (R2=0.78, p <0.01) (Fig.1). These results demonstrate that the electrical complexity in the dish increased with the culture time. Rotor dynamics (i.e. curvature and rotor movement) were significantly correlated with the amount of PSs in the cultures (R2=0.86 and R2=0.79 respectively, Fig. 1). Conclusion: Early and late stage HL-1 cell cultures present different degrees of electrophysiological complexity. Dynamics of functional reentries may be the main responsible for the increased complexity of remodeled cell cultures.